2015
DOI: 10.1177/0148607115571015
|View full text |Cite
|
Sign up to set email alerts
|

Revised Questionnaire to Assess Barriers to Adequate Nutrition in the Critically Ill

Abstract: The revised questionnaire to assess barriers to EN seems acceptable and clinically sensible and now appears to comprehensively list all possible modifiable barriers to delivering EN. This questionnaire needs further study to determine whether measuring barriers with this questionnaire can translate into improved EN delivery to critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Results showed that the total enteral feeding barriers score of ICU patients was 61.14 ± 12.77, while the item score was 3.22 ± 0.44. The respondents’ barrier levels when sufficient EN was provided to patients were at a moderate level, which is in agreement with the results of Cahill, Jiang, and Heyland (). The highest score among the three dimensions was delivery of EN to the patient.…”
Section: Discussionsupporting
confidence: 90%
“…Results showed that the total enteral feeding barriers score of ICU patients was 61.14 ± 12.77, while the item score was 3.22 ± 0.44. The respondents’ barrier levels when sufficient EN was provided to patients were at a moderate level, which is in agreement with the results of Cahill, Jiang, and Heyland (). The highest score among the three dimensions was delivery of EN to the patient.…”
Section: Discussionsupporting
confidence: 90%
“…Resistance to changing an established practice has been identified as one of the main barriers to implementing nutrition guideline recommendations . Inertia of previous practice (ie, “This is how I've always done it.”), fear of adverse events due to aggressive feeding (ie, poor outcome expectancy), lack of awareness or familiarity with current guidelines, lack of self‐efficacy, and reduced protocolization are examples of provider‐related behavior that may prevent adequate feeding in the ICU . Cabana et al have suggested clinicians’ lack of barriers knowledge may be an impediment to changing practice and without knowledge of such barriers, any interventions or guideline recommendations aimed at improving practice are unlikely to be successful.…”
Section: Provider Attitudes and Behaviormentioning
confidence: 99%
“…It is important to note that knowing the nutritional profile of patients before initiating therapy allows for appropriate diet planning, with the objective of fixing pre-existing nutritional deficiencies and meeting current nutritional demands (20)(21) . It is also necessary to investigate the variables that are associated with higher frequency of malnutrition and death, since these variables can help identifying groups that are more vulnerable to unfavorable outcomes (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Domain 04 -Control of complications emphasizes the need to identify failures in care or disagreements between the nursing staff to avoid mechanical, metabolic and/or digestive complications, since several factors can make it difficult to provide the necessary calories in enteral nutrition to severely ill patients (20). These factors are usually related to the lack of adequate information and qualified knowledge necessary for a safe assistance in enteral nutrition (11) .…”
Section: Discussionmentioning
confidence: 99%